Insufficient global health education in European neurological post‐graduate training: a European Association of Young Neurologists and Trainees survey. (1st August 2016) - Sauerbier, A.; Macerollo, A.; Györfi, O.; Balicza, P.; Moarcas, M.; Papp, V.; Zis, P.; Klingelhoefer, L.; Saifee, T.; Struhal, W.; Sellner, J.
Abstract : Background and purpose: The awareness of and demand for neurological expertise in global health (GH) have emerged over recent years and have become more relevant due to the increasing numbers of refugees from developing countries arriving in Europe. This study aimed to assess the provision of GH education and opportunities for international exchange during neurology post‐graduate training with a focus on Europe. Methods: We developed a questionnaire covering different aspects of and interest in GH education on behalf of the European Association of Young Neurologists and Trainees. Residents in neurology and junior neurologists (RJN) were approached to complete this survey. Results: Completed questionnaires were returned by 131 RJNs, of whom 65.7% were women and 84.0% were between 26 and 35 years old. In total, almost one‐third (29.0%) of RJNs reported that their residency programs offered training in GH. Limited education was reported for women's or children's health and neurological disorders of immigrants and refugees, as only 22.1%, 25.2% and 22.1% of RJNs reported that such training was offered, respectively. The curriculum rarely included coverage of the global impact of neurological disorders. Definite plans to volunteer in a developing country were reported by 7.6%. The majority of the participants acknowledged the importance of GH training and international exchange during post‐graduate education. Conclusion: This survey corroborates the interest in and appreciation of GH education by European RJNs. However, there are shortcomings in training and opportunities for international exchange. Academic neurology and international bodies, including the European Academy of Neurology, are requested to address this. Abstract : Clickhere to view the accompanying paper in this issue.